(untitled) (Bangladesh Pharmaceutical Journal, 2012)
In this present study, the leaf extracts of Parmentiera cereifera were subjected to a comparative evaluation of the antioxidant capacities, phenol and polyphenols content, membrane stabilization, thrombolytic, antimicrobial activities and cytotoxicity to brine shrimps (Artemia salina). When the DPPH (1,1- Diphenyl-2-picryl hydrazyl) radical scavenging effect was determined spectrophotometrically significant radical scavenging property was observed in crude methanol extract (ME) with IC50 of 21.95 ?g/ml. Here, butylated hydroxytoluene (BHT) and ascorbic acid (ASA) were used as standard antioxidants. The phenol and polyphenol content of the extractives varied between 56.84 to 89.58 mg of GAE/gm of dried extract. The thrombolytic and membrane stabilizing activities were assessed by using human erythrocyte and the results were compared with standard streptokinase (SK) and standard anti-inflammatory drug, acetyl salicylic acid (ASA), respectively. The extracts demonstrated significant toxicity to A. salina with LC50 values ranging from 6.07 to 7.83 ?g/ml as compared to standard Vincristine sulphate (VS, LC50 value 0.45 ?g/ml). On the other hand, the chloroform soluble fraction (CSF) of methanol extract revealed moderate antibacterial activity against some microorganisms used in the screening. Preliminary phytochemical investigation suggested the presence of flavonoids, saponins, tannins, triterpenoids and steroids. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12572 Bangladesh Pharmaceutical Journal 15(2): 103-106, 2012